2009
DOI: 10.1111/j.1537-2995.2009.02226.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ex vivo expansion culture conditions of mesenchymal stem cells for human cell therapy

Abstract: BACKGROUND:Mesenchymal stem cells (MSCs) are multipotent stem cells. Based on their properties, several clinical trials have been designed to explore their potential therapeutic effect. Fetal calf serum (FCS, commonly used for in vitro expansion) is an undesirable source of xenogeneic antigens and bears the risk of transmitting contaminations. As an alternative for FCS, platelet lysate (PL) and both autologous and allogeneic human serum have been proposed. The aim of this study is to compare the culture of bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 30 publications
3
58
1
Order By: Relevance
“…This effect, however, may not necessarily hold true in ‘humanized' culture systems. Similar to our own yet unpublished data, bFGF appears to support expansion of FBS-supplemented bone marrow MSC cultures, but fails to do so in HPL-supplemented systems [105]. Neutralization of PDGF-AB/BB, TGF-β1 and FGF significantly diminished the proliferative effect of HPL, with the strongest effects seen by neutralizing FGF alone or in combination with PDGF-BB [77].…”
Section: Platelet Lysatesupporting
confidence: 51%
“…This effect, however, may not necessarily hold true in ‘humanized' culture systems. Similar to our own yet unpublished data, bFGF appears to support expansion of FBS-supplemented bone marrow MSC cultures, but fails to do so in HPL-supplemented systems [105]. Neutralization of PDGF-AB/BB, TGF-β1 and FGF significantly diminished the proliferative effect of HPL, with the strongest effects seen by neutralizing FGF alone or in combination with PDGF-BB [77].…”
Section: Platelet Lysatesupporting
confidence: 51%
“…Those serum batches are similar due to extensive analysis of the manufacturer, but they are not equivalent. A further cause of heterogeneity is the use of human platelet lysate (hPL) for expansion of MSCs [25,[32][33][34][35][36]. Expansion in hPL is attractive because it does not contain animal components [32,35,37], which allows cells cultured in hPL to be used in clinical settings [38].…”
mentioning
confidence: 99%
“…4 Several clinical trials have been designed in an attempt to explore their therapeutic potential in acute graft-versus-host disease (GVHD), 5,6 while the information available on the efficacy of MSCs in the chronic GVHD setting is far more limited 7 (www.clinicaltrials.gov). We have previously shown that the expansion of MSC using human serum is feasible, 8 and their immunomodulatory properties were preserved and comparable with MSC expanded using FCS. In order to prevent viral or prion contamination, we designed a phase I/II clinical trial in order to evaluate the potential benefit of the infusion of MSC expanded using human serum (HS) among patients diagnosed with either refractory acute or chronic graft-versus-host dis- …”
Section: Introductionmentioning
confidence: 99%